Перші парафії УАПЦ в Одесі: функціонування та долі пастирів (1917–1938 рр.) - Михайлуца, М. (Краєзнавство, 2019)
У статті досліджується становлення й діяльність перших парафій Української автокефальної православної церкви в Одесі після революційних подій 1917–1921 рр. та в період репресій влади проти УАПЦ. За мету ставиться розгляд церковного локусу – автокефальних парафій в Одесі – Покрівської і Входо-Ієрусалимської, їх активних прихожан та священнослужителів. Джерельною основою студій є малознані, інформативно бідні й уривчасті, але сутнісно важливі для сьогодення, свідчення підслідних та жертв політичних репресій кінця 1920–1930-х рр. Реконструювання історії релігійних громад УАПЦ вимальовувалось на основі архівно-слідчих справ фонду Р-8065, які перебувають на зберіганні Держархіву Одеської області (ДАОО). Відкинуто ідеологічні, брехливо-міфологічні конструкції слідчих ДПУ– НКВС, завдяки методикам (порівняльного аналізу, історичної біографістики, історичної антропології), проаналізовано тексти обвинувачень і перехресних очних ставок, інші подібні фейки, подано персоніфіковано трагічне минуле одеських осередків автокефальної церкви, зроблено висновок про тяглість населення до української церкви й духовної єдності усіх регіонів України. The article is investigated the formation and activity of the first curacies of the Ukrainian Autocephalous Orthodox Church (UAOC) in Odessa after the revolutionary events of 1917–1921 and during the repressive actions of the Bolshevik authorities against the UAOC.The aim is considered peculiar of the church’s artifact – church-autocephalous curacies in Odessa – Pokrivska and Vhodo-Jerusalem. The research is concerned with visualizing its active figures and priests, from the perspective of playing locally civilization pictures, for which there is an inherent multidimensionality historical process, and man, its World-Church, as a microcosm, appearing in a broad social context and diverse manifestations. The source of our studies is non-space, often informationally poor and fragmentary, but essential for the present, testimony of those who are investigators and victims of political processes of the late 20s and 30s of the ХХ century. The reconstruction of the history of one or two Ukrainian autocephalous religious communities appeared to be too complicated, small, sometimes very segmental, driven in a few words by facts about people, events, church’s situation, etc. from a dozen archival and investigative cases of the R-8065,that they are kept by the State Archives of Odessa region (SAOR).Rejected ideological verbal dogmas of the past, falsely-mythological essay design of the commissioned officers of the DPU–NKVD, the phantom texts of accusations and cross-eye rates, and other similar fakey forms in puzzles and tragedy past the Odessa centers of the autocephalous church and people almost a hundred years ago.